Synthesis and Formation of T11223 and T1223 High-Tc Superconductors - Yahya, Ahmad Kamal; Abd Shukor, Roslan (Universiti Putra Malaysia Press, 2003)
The preparation methods of Tl2Ba2Ca2Cu30,o (T1l223) and Tlo.5Pbo.5Sr1.6Ca.4Cu30g (TI2223) superconductors using a variety of starting compositions and sintering temperatures are discussed. Single-phased Tl2223 with T, between 106 to 109 K can be prepared using T12Ba2C~Cu3010 and Tl1.6Ba2C~4Cu3010as starting compositions in a non-closed system by heating around 20 min at 910°C in flowing 02' Samples with Tl1223 major phase (- 70%) can be prepared from Tlo.5Pbo.5SrI.6C~.4Cu30gcomposition with the sample wrapped in gold foil and sintered in flowing oxygen at 940°C for 3 hours.